Sodium ferric phosphate pyrophosphate positive electrode material and preparation method thereof

By using phosphoric acid as a phosphorus source and dispersion regulator, combined with an aqueous system and a freeze-drying method, the problem of poor conductivity and rate performance of the material is solved, and its electrochemical performance and reversible specific capacity are significantly improved.

CN119503753APending Publication Date: 2025-02-25STATE GRID HUNAN ELECTRIC POWER COMPANY LIMITED +3
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411647545.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-18
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The cathode material of sodium ferric pyrophosphate has problems such as poor electronic conductivity and poor rate performance, and the carbon coating method leads to low capacity and high carbon content, which limits its large-scale production.

Method used

Phosphoric acid is used as the phosphorus source and dispersion regulator to prepare sodium ferrophosphate phosphate positive electrode material through an aqueous system and freeze-drying method to reduce the carbon coating content, improve the conductivity of the material and ion/electron transmission efficiency.

Benefits of technology

The electrochemical performance of sodium ferric pyrophosphate positive electrode material is significantly improved, including cycle stability and reversible specific capacity performance, solves the problems of poor conductivity and rate performance, and reduces production costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503753A_ABST
    Figure CN119503753A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of electrode materials, in particular to a sodium ferric pyrophosphate positive electrode material and a preparation method thereof, and the preparation method comprises the following steps: uniformly mixing phosphoric acid, an iron source, a sodium source and a carbon source in water, freeze-drying to obtain a precursor, and carbonizing to obtain the high-purity sodium ferric pyrophosphate positive electrode material. The preparation method provided by the invention can effectively improve the electrochemical performance of the ferric sodium pyrophosphate positive electrode material, and has very strong expansibility and application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electrode materials, and in particular to a sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof. Background Art

[0002] Sodium-ion batteries are electrochemical energy storage devices that use the shuttling of sodium ions between positive and negative electrodes to realize the battery's charge and discharge process. They are composed of a sandwich structure of positive electrode-electrolyte / diaphragm-negative electrode. Because of their similar working principles to lithium-ion batteries, sodium-ion batteries have received great attention in the research field. However, due to the difference in sodium ion radius and standard potential, the selection of materials for the positive and negative electrodes and supporting structures of sodium-ion batteries is not consistent with that of lithium-ion batteries. The main difference between the two is that the positive and negative electrode materials need to adapt to the larger ion radius of the sodium ion itself and provide a larger ion transmission channel. And because of the Na / Na + The higher standard electrode potential (-2.713V) allows the use of aluminum foil as the negative electrode current collector of sodium-ion batteries, which can further optimize the overall quality and cost of the battery system.

[0003] The positive electrode material plays a decisive role in the working voltage and energy density of the battery system. It mainly plays two roles. First, it provides sodium storage space for high-potential sodium ions and provides battery capacity. Second, it contributes to the working voltage of the battery. The difference between the redox potential of the positive and negative electrodes is the actual working voltage of the battery, which is also an important factor affecting the energy storage performance of the battery. At present, the positive electrode materials that have received more attention from researchers include polyanion positive electrode materials, transition metal oxide positive electrode materials, and Prussian blue derivative positive electrode materials.

[0004] Among them, polyanion cathodes have the advantages of low cost and good stability, and are considered to be the most commercially promising cathode materials for sodium-ion batteries. Sodium iron pyrophosphate cathode material (NFPP) has the advantages of low cost and stable structure, but it has the problems of poor electronic conductivity and poor rate performance. At present, the carbon coating method is mainly used to solve this problem, but it has the problems of low capacity and high carbon content, which seriously restricts its large-scale production.

[0005] Therefore, it is necessary to develop a sodium iron pyrophosphate positive electrode material with simple preparation process, excellent cycle stability and reversible specific capacity performance. Summary of the invention

[0006] In order to solve the above technical problems, the present invention provides a sodium iron phosphate pyrophosphate positive electrode material and a preparation method thereof, which can prepare a high-purity sodium iron phosphate pyrophosphate positive electrode material and significantly improve the electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode material.

[0007] In a first aspect, the present invention provides a method for preparing a sodium iron phosphate pyrophosphate positive electrode material, the preparation method comprising the following steps:

[0008] S1, dissolving phosphoric acid, an iron source, a sodium source and a carbon source in water to obtain a first solution, mixing, and freeze-drying to obtain a precursor;

[0009] S2. Carbonizing the precursor obtained in step S1 to obtain a sodium iron pyrophosphate positive electrode material.

[0010] The present invention uses phosphoric acid as a phosphorus source and a dispersion regulator, which can effectively promote the uniform distribution of various raw materials, and reduce the carbon content required for its coating while improving the purity of the sodium iron phosphate pyrophosphate crystal phase, thereby improving its electrochemical performance; the introduced water system effectively reduces the potential safety hazards in the production process; the freeze-drying method obtains a yellow precursor, maintains efficient dispersion and bonding between various raw material species, and makes the carbon layer coating uniform in the subsequent carbonization process better; the uniform coating structure can effectively improve the conductivity and ion / electron transmission efficiency of the sodium iron phosphate pyrophosphate positive electrode material, and alleviate the volume deformation occurring during the charge and discharge process, thereby significantly improving the electrochemical performance of the sodium iron phosphate pyrophosphate positive electrode material.

[0011] In some embodiments of the present invention, the phosphoric acid is added in the form of a phosphoric acid aqueous solution with a mass fraction of ≥75%. Low concentration of hydrochloric acid will reduce the solid content of the system and greatly increase the production cost.

[0012] In some embodiments of the present invention, the iron source is selected from any one of ferrous oxalate and ferrous chloride, or a combination of several of them.

[0013] In some embodiments of the present invention, the sodium source is selected from any one or a combination of sodium acetate, sodium carbonate, and sodium oxalate.

[0014] In some embodiments of the present invention, the carbon source is selected from any one or a combination of glucose, sucrose, and carbon quantum dots.

[0015] In some embodiments of the present invention, the molar ratio of the phosphorus element in the phosphoric acid, the iron element in the iron source, and the sodium element in the sodium source is 4:3:(3.5-4.5), for example, 4:3:3.6, 4:3:3.8, 4:3:4, 4:3:4.2, 4:3:4.4, etc.

[0016] In some embodiments of the present invention, the total mass of the phosphoric acid, iron source, sodium source and carbon source is 10-50% of the first solution, such as 15%, 25%, 35%, 45%, etc.

[0017] The entire reaction system of step S1 of the present invention is carried out in water, and no organic solvent is required, which can greatly reduce the cost of raw materials and the cost of treating organic waste liquid.

[0018] In some embodiments of the present invention, the pH of the first solution is less than 5.

[0019] In some embodiments of the present invention, the mixing method is ball milling.

[0020] In the present invention, phosphoric acid is used as the phosphorus source, and mechanical ball milling is used to evenly mix the iron source, phosphoric acid, sodium source and carbon source materials. The acidity of phosphoric acid is used to fully dissolve the iron source to achieve the purpose of efficient dispersion, thereby realizing molecular-level dispersion and coordination of phosphorus species and iron species.

[0021] In some embodiments of the present invention, the ball milling time is 4-6 hours, such as 4.5 hours, 5 hours, 5.5 hours, etc.

[0022] In some embodiments of the present invention, the rotation speed of the ball mill is 1000-2000 r / min, for example, 1200 r / min, 1400 r / min, 1600 r / min, 1800 r / min, etc.

[0023] In some embodiments of the present invention, the freeze-drying time is 10-24 hours, for example, 12 hours, 14 hours, 16 hours, 18 hours, 20 hours, 22 hours, etc.

[0024] The invention maintains efficient dispersion and bonding between various raw material species in the mechanical ball milling process through freeze drying, so that the carbon layer has better wrapping uniformity in the subsequent carbonization process, which is conducive to improving its purity.

[0025] In some embodiments of the present invention, the carbonization treatment is performed in an inert gas atmosphere.

[0026] The carbonization treatment described in the present invention refers to heating the precursor obtained in step S1 under the protection of an inert gas to cause a high-temperature solid-phase reaction, so that the precursor is converted into a carbon-coated positive electrode material.

[0027] In some embodiments of the present invention, the inert gas is selected from one or more of nitrogen, argon, helium, neon, and krypton.

[0028] In some embodiments of the present invention, the temperature of the carbonization treatment is 400-900°C, such as 500°C, 600°C, 700°C, 800°C, etc.

[0029] In some embodiments of the present invention, the carbonization treatment time is 6-12 hours, for example, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, etc.

[0030] In a second aspect, the present invention provides a sodium iron phosphate pyrophosphate positive electrode material prepared by the preparation method described in the first aspect.

[0031] In some embodiments of the present invention, the mass content of carbon element in the sodium iron pyrophosphate positive electrode material is 1-6%, such as 2%, 3%, 4%, 5%, etc.

[0032] The chemical composition of the sodium iron phosphate pyrophosphate positive electrode material described in the present invention is Na4Fe3(PO4)2P2O7@C.

[0033] In a third aspect, the present invention provides an electrochemical energy storage device, wherein the positive electrode material of the electrochemical energy storage device includes the sodium iron phosphate pyrophosphate positive electrode material described in the second aspect.

[0034] In some embodiments of the present invention, the electrochemical energy storage device includes any one of a sodium ion battery, a sodium ion capacitor, and a hybrid ion battery.

[0035] The electrochemical energy storage device provided by the present invention has more excellent cycle stability and reversible specific capacity.

[0036] The technical solution provided by the embodiment of the present invention has the following advantages compared with the prior art:

[0037] The preparation method provided by the present invention uses phosphoric acid as a phosphorus source and a dispersion regulator, which can not only improve the crystal phase purity of the prepared sodium iron phosphate pyrophosphate positive electrode material but also reduce the carbon coating content, thereby preparing a high-purity sodium iron phosphate pyrophosphate positive electrode material.

[0038] The sodium iron phosphate pyrophosphate positive electrode material prepared by the present invention has significantly improved electrochemical performance, wherein the cycle stability and reversible specific capacity performance are excellent.

[0039] The preparation method provided by the present invention has simple process, strong scalability, and broad prospects for application in the field of sodium ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate embodiments consistent with the invention and, together with the description, serve to explain the principles of the invention.

[0041] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, for ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0042] Figure 1This is the XRD diagram of the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention;

[0043] Figure 2 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention;

[0044] Figure 3 This is the XRD diagram of the sodium iron phosphate pyrophosphate positive electrode material described in Example 2 of the present invention;

[0045] Figure 4 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material described in Example 2 of the present invention;

[0046] Figure 5 This is the XRD diagram of the sodium iron phosphate pyrophosphate positive electrode material described in Comparative Example 1 of the present invention;

[0047] Figure 6 This is a cycle performance diagram of a sodium ion battery prepared with the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention at 0.5C;

[0048] Figure 7 The charge and discharge curves of the sodium ion battery prepared with the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention at different rates;

[0049] Figure 8 This is a charge and discharge curve diagram of a sodium ion battery prepared with the sodium iron phosphate pyrophosphate positive electrode material described in Comparative Example 1 of the present invention at different rates. DETAILED DESCRIPTION

[0050] In order to more clearly understand the above-mentioned objectives, features and advantages of the present invention, the scheme of the present invention will be further described below. It should be noted that the embodiments of the present invention and the features in the embodiments can be combined with each other without conflict.

[0051] In the following description, many specific details are set forth to facilitate a full understanding of the present invention, but the present invention may also be implemented in other ways different from those described herein; it is obvious that the embodiments in the specification are only part of the embodiments of the present invention, rather than all of the embodiments.

[0052] Example 1

[0053] This embodiment provides a sodium iron phosphate pyrophosphate positive electrode material, and the preparation method thereof is as follows:

[0054] S1. Dissolve 0.2mmol phosphoric acid (converted from 85% mass fraction phosphoric acid solution), 0.15mmol ferrous oxalate, 0.2mmol sodium acetate, and 0.03mmol glucose in 20mL deionized water, then transfer them into a ball mill, and perform mechanical ball milling at a speed of 1200r / min for 4h to obtain a yellow uniform slurry. Subsequently, transfer the slurry into a freeze dryer and freeze-dry for 12h to obtain a yellow precursor material.

[0055] S2. The yellow precursor dry powder prepared in S1 is heated at 550° C. for 6 h under nitrogen protection to obtain sodium iron phosphate pyrophosphate positive electrode material.

[0056] Example 2

[0057] This embodiment provides a sodium iron phosphate pyrophosphate positive electrode material, and the preparation method thereof is as follows:

[0058] S1, 0.6mmol phosphoric acid (converted from 75% mass fraction phosphoric acid solution), 0.45mmol ferrous chloride, 0.3mmol sodium carbonate, and 0.08mmol sucrose were dissolved and dispersed in 60mL deionized water, and then transferred to a ball mill and mechanically ball milled at 1500 rpm for 6h to obtain a yellow uniform slurry. The slurry was then transferred to a freeze dryer and freeze-dried for 12h to obtain a yellow precursor material.

[0059] S2. The precursor powder obtained in S1 is heated at 600° C. under argon protection for 8 h to obtain sodium iron phosphate pyrophosphate positive electrode material.

[0060] Example 3

[0061] This embodiment provides a sodium iron phosphate pyrophosphate positive electrode material, and the preparation method thereof is as follows:

[0062] S1, 0.6mmol phosphoric acid (converted from 75% mass fraction phosphoric acid solution), 0.45mmol ferrous chloride, 0.32mmol sodium oxalate, and 0.12mmol sucrose were dissolved and dispersed in 40mL deionized water, and then transferred to a ball mill and mechanically ball milled at 1500 rpm for 5h to obtain a yellow uniform slurry. The slurry was then transferred to a freeze dryer and freeze-dried for 10h to obtain a yellow precursor material.

[0063] S2. The precursor powder obtained in S1 is heated at 900° C. for 12 hours under helium protection to obtain sodium iron phosphate pyrophosphate positive electrode material.

[0064] Comparative Example 1

[0065] This comparative example provides a sodium iron phosphate pyrophosphate positive electrode material, and its preparation method is different from that of Example 1 in that phosphoric acid is replaced by the same molar amount of ammonium dihydrogen phosphate.

[0066] Comparative Example 2

[0067] This comparative example provides a sodium iron phosphate pyrophosphate positive electrode material, and its preparation method is different from that of Example 1 in that phosphoric acid is replaced by the same molar amount of sodium dihydrogen phosphate.

[0068] Performance Testing

[0069] 1. XRD and SEM testing

[0070] The sodium iron phosphate pyrophosphate positive electrode materials prepared in Examples 1, 2 and Comparative Example 1 were subjected to XRD and SEM tests, and the test results were as follows: Figure 1-5 shown.

[0071] Figure 1 This is the XRD diagram of the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention. Its characteristic peaks are consistent with the standard card peaks of sodium iron phosphate pyrophosphate (NFPP), and there are no other impurity peaks, indicating that a pure phase sodium iron phosphate pyrophosphate material is obtained. Figure 2 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention. It can be observed that it is in the shape of nano-scale examples. Figure 3 The XRD diagram of the sodium iron phosphate pyrophosphate positive electrode material described in Example 2 of the present invention is consistent with the standard card peak of sodium iron phosphate pyrophosphate (NFPP), and there are no other impurity peaks, indicating that the obtained material is also a pure phase sodium iron phosphate pyrophosphate material. Figure 4 This is a SEM image of the sodium iron phosphate pyrophosphate positive electrode material described in Example 2 of the present invention, and it can be observed that it is in the shape of a nano-example. Figure 1-4 It can be seen that the sodium iron phosphate pyrophosphate positive electrode material prepared using phosphoric acid as a phosphorus source has a crystal composition of pure phase sodium iron phosphate pyrophosphate.

[0072] Figure 5 The XRD diagram of the sodium iron phosphate pyrophosphate positive electrode material described in Comparative Example 1 of the present invention is shown in FIG. Figure 5 It can be seen that when phosphoric acid is replaced by the same amount of ammonium dihydrogen phosphate, its crystal composition is very impure and there is a very obvious impurity phase.

[0073] 2. Cycle performance and rate performance testing

[0074] Preparation of positive electrode sheet: Take the sodium iron phosphate pyrophosphate positive electrode material, conductive agent (Super P), and binder (PVDF) prepared in the embodiment and comparative example in a mass ratio of 8:1:1, disperse them in an organic solvent (NMP), and prepare slurry by homogenization. Then, use a scraper to apply the slurry on a copper foil with a thickness of 18 μm, and vacuum dry at 140°C for 12 h to obtain a electrode sheet, which is then cut into electrode sheets with a diameter of 14 mm.

[0075] Preparation of sodium ion battery: button cell method was used for testing, and the prepared electrode sheet was used as the positive electrode to assemble the sodium ion battery. The assembly order of the battery components was: negative electrode shell-gasket-sodium sheet-glass fiber diaphragm-positive electrode sheet-positive electrode shell. The electrolyte used was 1 mol / L NaPF6, and the solvent was ethylene carbonate (EC) / dimethyl carbonate (DMC) (volume ratio 1:1).

[0076] The prepared sodium ion battery was tested for cycle performance and rate performance. The test method is as follows: at 1.7–4.3V (vs. Na + / Na) voltage range, 0.5C (1C = 129mAh g -1 ) current conditions, constant current charge and discharge tests were carried out on the target material.

[0077] The specific test results are shown in Table 1 and Figure 6-8 shown.

[0078] Table 1

[0079]

[0080] Figure 6 This is a cycle performance diagram of a sodium ion battery prepared with the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention at 0.5C, Figure 7 The charge and discharge curves of the sodium ion battery prepared with the sodium iron phosphate pyrophosphate positive electrode material described in Example 1 of the present invention at different rates (blue, red, and black are 1C, 0.5C, and 0.1C, respectively). Figure 8 This is a charge and discharge curve diagram of a sodium ion battery prepared with the sodium iron phosphate pyrophosphate positive electrode material described in Comparative Example 1 of the present invention at different rates (blue, red, and black are 1C, 0.5C, and 0.1C, respectively).

[0081] From Table 1 and Figure 6 , Figure 7 It can be seen that the sodium iron phosphate pyrophosphate positive electrode material obtained by the preparation method of the present invention exhibits excellent rate performance and cycle performance at rates of 0.1C, 0.5C, and 1C.

[0082] From Table 1 and Figure 8It can be seen that the sodium iron pyrophosphate positive electrode material obtained by the comparative example preparation method exhibits lower rate performance at rates of 0.1C, 0.5C, and 1C.

[0083] In summary, the preparation method provided by the present invention can prepare high-purity sodium iron phosphate pyrophosphate positive electrode material, and the electrochemical performance is significantly improved, among which the cycle stability and reversible specific capacity performance are excellent.

[0084] It should be noted that, in this article, relational terms such as "first" and "second" are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.

[0085] The above description is only a specific embodiment of the present invention, so that those skilled in the art can understand or implement the present invention. Various modifications to these embodiments will be apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments described herein, but should conform to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a sodium iron phosphate pyrophosphate positive electrode material, characterized in that: The preparation method comprises the following steps: S1, dissolving phosphoric acid, an iron source, a sodium source and a carbon source in water to obtain a first solution, mixing, and freeze-drying to obtain a precursor; S2. Carbonizing the precursor obtained in step S1 to obtain a sodium iron pyrophosphate positive electrode material.

2. The preparation method according to claim 1, characterized in that: The phosphoric acid is added in the form of a phosphoric acid aqueous solution having a mass fraction of ≥75%; Preferably, the iron source is selected from any one or a combination of ferrous oxalate and ferrous chloride; Preferably, the sodium source is selected from any one or a combination of sodium acetate, sodium carbonate, and sodium oxalate; Preferably, the carbon source is selected from any one or a combination of glucose, sucrose and carbon quantum dots.

3. The preparation method according to claim 1 or 2, characterized in that: The molar ratio of phosphorus in the phosphoric acid, iron in the iron source, and sodium in the sodium source is 4:3:(3.5-4.5); Preferably, the total mass of the phosphoric acid, iron source, sodium source and carbon source is 10-50% of the mass of the first solution; Preferably, the pH of the first solution is <5.

4. The preparation method according to any one of claims 1 to 3, characterized in that: The mixing method is ball milling; Preferably, the ball milling time is 4-6h; Preferably, the rotation speed of the ball mill is 1000-2000r / min; Preferably, the freeze-drying time is 10-24 hours.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The carbonization treatment is carried out in an inert gas atmosphere; Preferably, the inert gas is selected from one or more of nitrogen, argon, helium, neon and krypton.

6. The preparation method according to any one of claims 1 to 5, characterized in that: The temperature of the carbonization treatment is 400-900°C; Preferably, the carbonization treatment time is 6-12 hours.

7. A sodium iron phosphate pyrophosphate positive electrode material, characterized in that The invention is prepared by the preparation method according to any one of claims 1 to 6.

8. The sodium iron phosphate pyrophosphate positive electrode material according to claim 7, characterized in that The mass content of carbon element in the sodium iron pyrophosphate positive electrode material is 1-6%.

9. An electrochemical energy storage device, characterized in that: The positive electrode material of the electrochemical energy storage device includes the sodium iron phosphate pyrophosphate positive electrode material according to claim 7 or 8.

10. The electrochemical energy storage device according to claim 9, characterized in that: The electrochemical energy storage device includes any one of a sodium ion battery, a sodium ion capacitor, and a hybrid ion battery.

Citation Information

Cited By

  • Sodium-rich ferric sodium pyrophosphate positive electrode precursor as well as preparation method and application thereof

    CN120607235A